S is for Stranger - 11 Erotic Short Stories - Hart, Venessa (Saga Egmont, 2023)
‘S is for Stranger - 11 Erotic Short Stories’ is a collection of erotica that explores the pleasures of getting to know a stranger purely through their body and sexual desires.